Leadership of Covid-19 in the Transaction of Vegetables at Kathmandu Valley in Nepal - Karki, Mr. Meen Bahadur (The journal of contemporary issues in business and government, 2023)
The Covid-19 has affected the global community to a large extent and more precisely the consumable sector. The primary goal of this study is to determine how the Covid 19 pandemic has affected the sales and consumption of vegetables in the Kalimati Fruits and Vegetable Market in Kathmandu, Nepal. Also, it intends to determine how many kinds of green vegetables are supplied to residents of the Kathmandu Valley and what substitutions they have made in their kitchens to make up for the shortage. The study included 102 gate visitors to central fruit and vegetable market as respondents for data collection. The analysis revealed that during the hours of vegetable pick-up, only 20-40% of the whole regular supply is available, and vegetable prices have increased by 11-66%. Most of the locals replaced the green vegetables in their houses with locally preserved veggies instead of pulses, grains, dals, paneer, and dry beans. Moreover, majority of the respondents recommended preserving eatable veggies during bumper crop times for replenishment at times of crisis like Corona and even during periods of natural scarcity. The present study emphasizes on providing a learning towards sustaining in a crisis situation.